Developing Electronic Portfolios to Align with Diverse National Standards to Showcase Students’ and Teachers’ Performance: A Design Approach - FABUNMI Olaiya, Kazeem; Ogunlade, Oyeronke O. (Innovare Journal of Education, 2023)
Traditional methods of documenting and assessing educational performance and achievements have often been limited in scope and accessibility. Addressing these limitations is to leverage the potential of technology to create a comprehensive and user-friendly electronic portfolio (e-portfolio) system. This study aimed to investigate the required national standard and functionalities of e-portfolios for showcasing students’ and teachers’ performance. This study adopted qualitative research methods to investigate the context under study. Interviews, documents, and reports with and from students, lecturers, administrators, and educational experts provided insights into the specific requirements and expectations for an effective electronic portfolio system. One hundred twenty-five participants were randomly sampled for the study in the Abuja metropolis of Nigeria. Data were collected using a semi-structured interview and case study approach. A deductive approach was employed for the coding and analysis of the transcribed data. The findings identified several key features and functionalities required in an electronic portfolio system: Customizability and Flexibility, Alignment with Standards, Multimedia Capabilities, Reflection, and Goal-Setting Tools. Both students and teachers generally perceived the use of electronic portfolios positively. The respondents highlighted technological barriers, such as lack of necessary skills, limited access to devices or reliable internet connectivity; time constraints; and resistance to change as challenges in using e-portfolios to showcase their performance. Based on a systematic analysis of interview data from the respondents, the qualitative study offers a framework for exploring, understanding, and discussing the standard for and the impact of developing electronic portfolios for student and teacher performance.